Cublak-cublak Suweng Game: Can it Improve the Socio-emotional Development of Alpha Generation Children? - Hasni, Nazlah; Ni’matuzahroh, Ni’matuzahroh; Karmiyati, Diah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Games are a natural way for children to learn and develop physically, cognitively and socio-emotionally. Traditional games are a learning medium that has many benefits for children's development. This research aims to find out how the traditional game